Following Brodsky. Andrey Zvyagintsev’s Apocrypha - Waligórska-Olejniczak, Beata (Studia Rossica Posnaniensia, 2021)
The article presents the study of the short film Apocrypha by Andrei Zvyagintsev. The text is aimed at the interpretation of the movie in the context of the problem of memory, which is emphasised in the selected work in the explicit and implicit visual associations with the figure and poetry of Iosif Brodsky. The recognition of these characteristic elements in the structure of Zvyagintsev’s film has the influence on the perception of its meaning, leading the culturally aware recipient towards discovering its broad interpretative potential in view of the Russian literary tradition. The study is conducted using the comparative method of analysis. The core theory which constitutes the methodological foundation of the study is Astrid Erll’s concept of cultural memory expounded as intertextuality, i.e. the continuous building up of layers of texts, which are mediated, as well as her idea of transcultural memory, defined in the first instance as a process of fluctuation between the individual and collective level of remembering. Attention is turned to the motifs, which are characteristic both for Brodsky’s and Zvyagintsev’s poetics, such as the aquatic symbolism, temporal and topographical relationships, chromatography of cold colours etc. The application of the selected methodology in the presented discussion allows for exposing the dynamics of the changing nature of culture, which becomes the container of the social and territorial fluctuations of memory.